A szólás- és tanszabadság elve a mózesi Törvényben és a rabbinikus jogban - Ruff, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The Torah law and rabbinic jurisprudence are the decisive (and only explicit) starting points for the researcher in the study of the principle of freedom of speech and teaching. Their partial collision in the history of interpretation and jurisprudence of Judaism led, in a fruitful way, to the recognition and enforcement of freedom of conscience and, consequently, of the principles of freedom of speech and teaching, already in antiquity – not without restrictions in the theocratic state, but widely within the framework of the Torah. In exploring these boundaries, we will also gain insight into one of the interpretation methods of the Torah as an unappealable source of law with divine authority in all its words, the so-called pilpul, which unfolded in rabbinic legal hermeneutics.